Pengembangan Soal HOTS-PISA dan LKPD Deep Learning untuk Pembelajaran Fisika bagi Guru Fisika SMA/MA Se Provinsi Lampung - Viyanti; Abdurrahman Abdurrahman; Anggreini Anggreini; Dimas Permadi; Ike Festiana; Adelia Adelia; Erma Novela; Emi Gustina (Ruang Pengabdian: Jurnal Pengabdian kepada Masyarakat, 2025)
This community service program aims to enhance the professional competence of senior high school (SMA/MA) Physics teachers across Lampung Province in developing test items oriented toward Higher Order Thinking Skills (HOTS) and in adapting questions from international studies such as TIMSS (Trends in International Mathematics and Science Study) and PISA (Programme for International Student Assessment). The technical training was conducted through a combination of training sessions and workshops, covering the following components: an introduction to the characteristics of HOTS-based questions, strategies for designing HOTS-oriented items aligned with the Merdeka Curriculum, analysis of the structure and context of TIMSS/PISA questions, and hands-on practice in adapting and developing test items by participants. This activity involved Physics teachers from various districts and cities throughout Lampung Province and was carried out in person (face-to-face). During the training, participants received direct guidance and feedback from a team of experts. The results of the program showed significant improvement in participants' understanding of HOTS concepts and their ability to develop questions that require higher-order, analytical, and contextual thinking, in line with international assessment standards. It is expected that this initiative will contribute to improving the quality of Physics education and better preparing students for both national and international assessments.